The Effect of Organizational Climate and Self-Efficacy on Organizational Commitment with Job Satisfaction as a Mediating Variable: An Empirical Study on Employees in the Multifinance Industry in Jakarta - Joko Ariawan; Didik Notosudjono; Widodo Sunaryo (Dinasti Publisher, 2026)
This study aims to examine the impact of Organizational Climate and Self-Efficacy on Organizational Commitment, with Job Satisfaction acting as a mediating variable. The research population consisted of 1,294 permanent employees in multifinance companies in Jakarta, with a sample of 248 selected through proportional random sampling. A mixed-methods approach was employed, combining quantitative analysis using Path Analysis with qualitative insights from the Delphi technique to gather expert input from human resource practitioners. The results indicate that Organizational Climate and Self-Efficacy positively and significantly influence Organizational Commitment directly. In addition, both variables also have positive and significant indirect effects on Organizational Commitment through Job Satisfaction, although the mediating role of Job Satisfaction was found to be less effective. The findings highlight that supportive supervision, employee confidence in competencies, and promotion opportunities are key aspects of Job Satisfaction that strengthen commitment. Based on these results, Human Resources policymakers are advised to prioritize strategies that enhance Organizational Climate through clear work structures and supervisory support, develop Self-Efficacy by increasing task confidence and scope, and improve Job Satisfaction via promotion opportunities, compensation, and effective supervision. These interventions are essential for sustaining employee performance and retention in the dynamic multifinance industry.